Contributions of Entrepreneurial Universities to the Triple Helix: discursive textual analysis using IRAMUTEQ Software - Cerqueira, Gabriel de Oliveira (2024)
The present study aims to analyze the Triple Helix model in the Brazilian context in entrepreneurial universities through Discursive Textual Analysis (DTA). The textual data were collected in the Scopus and Web of Science databases, the Boolean expression used brought together works that address the theme of entrepreneurial universities in Brazil. The textual corpus was constructed from abstracts of texts collected in the databases. The ATD was carried out with the support of the IRAMUTEQ Software in which the steps of unitarization, categorization and identification of statistical relationships, production of metatexts and capture of emergent were carried out, resulting in word clouds, dendrograms and word clusters that allowed analysis of the most recurrent words in publications and their relationships, highlighting the role of entrepreneurial universities in creating and disseminating knowledge and technology to promote entrepreneurship and innovation among students and collaborating with the business sector.